THE EFFECT OF PATIENT COOPING MECHANISM ON ANXIETY IN DEALING WITH MAJOR SURGERY IN THE SURGERY INPATIENT ROOM OF PUSKESMAS TIGA BALATA JORLANG HATARAN DISTRICT YEAR 2016 - Nurmala (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
Patients with a history of hypertension when experiencing anxiety before surgery can result in insomnia of the patient and the blood pressure will increase so that the operation will be canceled. Surgery or surgery can cause anxiety. Anxiety is a normal adaptive response to stress due to surgery. Anxiety can be reduced what if the patient can see the surgery will heal. Signs of anxious surgery may not be the same for every individual. Every stress cause people to experience, for the automatic appears efforts to cope with a variety of coping mechanisms, to control coping and decrease anxiety in patients is the task of the team. Served in the room where the patients were treated. Having interactions to patients to anxiety in the face of major surgery that ascribed by Tiga Balata Health Center, Kec. Jorlang Hataran of 2016. The experience is descriptive analytic with the experience design cross sectional. Take in population in this study were an patients who ascribed. To undergo surgery used in this study is a questionnaire filled by respond. After the data was collected then for the percentage of data used by ghi-sguare a - 0.05 with the computer Which then obtained the effect of each independent variable. The result of data analysis and the result of ghi-sguare is P — 0.001 (P « 0.005), is Ha is accept and Ho is eject, is patient influence between the coping mechanisms of the anxiety in the face major operation. 05 with the computer Which then obtained the effect of each independent variable. The result of data analysis and the result of ghi-sguare is P — 0.001 (P « 0.005), is Ha is accept and Ho is eject, is patient influence between the coping mechanisms of the anxiety in the face major operation. 05 with the computer Which then obtained the effect of each independent variable. The result of data analysis and the result of ghi-sguare is P — 0.001 (P « 0.005), is Ha is accept and Ho is eject, is patient influence between the coping mechanisms of the anxiety in the face major operation.